Evaluation of Serum and Urinary Neutrophil Gelatinase Associated Lipocalin (NGAL) in Children with Nephrotic Syndrome (Medico Legal Update, 2020)
Background: Nephrotic syndrome in children is a common disease in the world, and is a group of clinicalsymptoms and include (loss of protein in the urine, low protein level in the blood, the accumulation of fluidin the body or edema, and high blood lipids). The cause of Nephrotic Syndrome is unknown. Neutrophilgelatinase associated lipocalin is a protein encoded in humans by the LCN2 gene. NGAL interferes withnatural immunity by blocking iron, causing the growth of germs to be reduced. It is expressed in kidney,prostate, respiratory and digestive cells. NGAL is used as a vital guide to kidney injury.Method: Neutrophil gelatinase-associated lipocalin concentration was measured in blood plasma usingenzyme-linked immunosorbent assay (ELISA) and urine NGAL by Abbott i1000, measured plasma andurine level of NGAL in 20 patients with steroid resistance nephrotic syndrome,20 patients with steroidsensitive nephrotic syndrome, 17 patients with early diagnosed nephrotic syndrome compare with 20 healthyvolunteers enlisted as normal controls.Results: Urine NGAL and plasma NGAL are significantly increase in SRNS, SSNS, EDNS compared withcontrol group.Conclusion: NGAL can be used to diagnostic biomarker to predict steroid Sensitive or steroid resistance inchildren with Nephrotic syndrome (NGAL is a differentiating marker between SSNS and SRNS).